Bilateral impairments in task-dependent modulation of the long-latency stretch reflex following stroke - Trumbower, Randy D. (2013)
OBJECTIVE: Modulation of the long-latency reflex (LLR) is important for sensorimotor control during interaction with different mechanical loads. Transcortical pathways usually contribute to LLR modulation, but the integrity of pathways projecting to the paretic and non-paretic arms of stroke survivors is compromised. We hypothesize that disruption of transcortical reflex pathways reduces the capacity for stroke survivors to appropriately regulate the LLR bilaterally. METHODS: Elbow perturbations were applied to the paretic and non-paretic arms of persons with stroke, and the dominant arm of age-matched controls as subjects interacted with Stiff or Compliant environments rendered by a linear actuator. Reflexes were quantified using surface electromyograms, recorded from biceps. RESULTS: LLR amplitude was significantly larger during interaction with the Compliant load compared to the Stiff load in controls. However, there was no significant change in LLR amplitude for the paretic or non-paretic arm of stroke survivors. CONCLUSIONS: Modulation of the LLR is altered in the paretic and non-paretic arms after stroke. SIGNIFICANCE: Our results are indicative of bilateral sensorimotor impairments following stroke. The inability to regulate the LLR may contribute to bilateral deficits in tasks that require precise control of limb mechanics and stability.